Seismic strengthening of beam-column joints with multidirectional CFRP laminates - Coelho, M. (2012)
An experimental program was carried out to analyse the potentialities of a technique based on the use of multidirectional CFRP laminates (MDL-CFRP) for the seismic repair and strengthening of reinforced concrete (RC) beam-column joints. This experimental program comprises cyclic tests on three full-scale RC joints, representative of interior beam-column connections in buildings. The joints were initially submitted to a cyclic test inducing a damage pattern representative of a seismic event. Subsequently, they were repaired and strengthened with MDL-CFRP. The strengthened joints were then tested for the same loading history of the original ones up to their failure. The adopted strengthening technique uses the MDL-CFRP that are simultaneously glued and anchored to the concrete surfaces. This technique is called Mechanically Fastened and Externally Bonded Reinforcement (MF-EBR). In the present study, the effectiveness of two different strengthening configurations was investigated. The tests are described and the main results are presented and analyzed.